2008
DOI: 10.1148/radiol.2483071863
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Nephrogenic Systemic Fibrosis at Two Large Medical Centers

Abstract: For patients with an eGFR lower than 15 mL/min, hemodialysis helped to prevent NSF. For patients with an eGFR lower than 30 mL/min who received a high dose of GBCA, acute renal failure, delayed hemodialysis after contrast agent injection, proinflammatory events, and hyperphosphatemia were associated with increased risk of NSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
209
0
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(220 citation statements)
references
References 40 publications
5
209
0
6
Order By: Relevance
“…In vivo major differences between the different GBCAs with regard to short-and long-term Gd skin concentrations and in the propensity to induce skin lesions have been described. Interestingly, also in clinical studies similar differences between the GBCAs and the risk to induce NSF were reported (52,53).…”
Section: Discussionsupporting
confidence: 52%
“…In vivo major differences between the different GBCAs with regard to short-and long-term Gd skin concentrations and in the propensity to induce skin lesions have been described. Interestingly, also in clinical studies similar differences between the GBCAs and the risk to induce NSF were reported (52,53).…”
Section: Discussionsupporting
confidence: 52%
“…One article looked at the difference in NSF risk with acute renal failure between injecting high-dose GBCA while serum creatinine was rising (NSF incidence ¼ 19%) versus injecting after serum creatinine had peaked (0 cases of NSF in 41 patients) or after regular hemodialysis was started (0 cases of NSF in 32 patients) (57). This suggests that NSF risk can be substantially reduced in acute renal failure patients by either dialyzing shortly after GBCA injection or by delaying the MRI until after the serum creatinine has peaked and the renal failure is beginning to resolve.…”
Section: Acute Vs Chronic Renal Failurementioning
confidence: 99%
“…This is consistent with the widely held belief that prompt effective dialysis protects against NSF. The only article addressing this topic on patients receiving high-dose GBCA reports a 0.4% incidence of NSF in dialysis patients and 0% incidence if the dialysis is performed within 24 hours of high-dose GBCA administration, but an 8.8% incidence of NSF in patients with GFR <15 mL/ min who are not on dialysis at the time of high-dose GBCA (57). These data support the hypothesis that prompt dialysis reduces NSF risk, perhaps on the order of 20-fold.…”
Section: Timely Dialysismentioning
confidence: 99%
“…Specifically, in this serum system there were differences in the release of Gd between Magnevist and Omniscan (Magnevist behavior appeared to be similar to the macrocyclic GBCA Dotarem and ProHance) but both Magnevist and Omniscan are associated with the greatest number of cases of NSF. The theory also does not take into account many other patient-associated factors thought to play a role-not least the fact that only a small minority of ESRD patients develop NSF (2,5). Other observations that demonstrate that other factors play a significant role in the development of NSF include:…”
Section: The Phagocytosis Of Gd Triggers Inflammatorymentioning
confidence: 99%
“…To date, it has only been reported in patients with severely impaired renal function (SIRF), endstage renal disease (ESRD), and those in acute renal failure (ARF) (2)(3)(4)(5). The many other risk factors thought to be associated with NSF include: edema (6), metabolic acidosis, thrombotic events, high-dose erythropoietin (EPO) (7,8), systemic inflammation (9), recent surgery, kidney disease (10), and gadolinium (Gd 3þ )-based contrast agent (GBCA) exposure (11,12), especially when used at relatively high dose GBCA (5,13). NSF, which was first recognized by Cowper et al (1) and linked to GBCA in 2006 (11), is characterized by induration, thickening, and tightening of the skin.…”
mentioning
confidence: 99%